Association between cerebrospinal fluid clusterin and biomarkers of Alzheimer’s disease pathology in mild cognitive impairment: a longitudinal cohort study - Wang, Hao; Ma, Ling-Zhi; Sheng, Ze-Hu; Liu, Jia-Yao; Yuan, Wei-Yu; Guo, Fan; Zhang, Wei; Tan, Lan (Frontiers in Aging Neuroscience, 2023)
Background: Clusterin, a glycoprotein implicated in Alzheimer's disease (AD), remains unclear. The objective of this study was to analyze the effect of cerebrospinal fluid (CSF) clusterin in relation to AD biomarkers using a longitudinal cohort of non-demented individuals. Methods: We gathered a sample comprising 86 individuals under cognition normal (CN) and 134 patients diagnosed with MCI via the Alzheimer's Disease Neuroimaging Initiative (ADNI) database.To investigate the correlation of CSF clusterin with cognitive function and markers of key physiological changes, we employed multiple linear regression and mixed-effect models. We undertook a causal mediation analysis to inspect the mediating influence of CSF clusterin on cognitive abilities.Results: Pathological characteristics associated with baseline Aβ42, Tau, brain volume, exhibited a correlation with initial CSF clusterin in the general population, Specifically, these correlations were especially prominent in the MCI population; CSF Aβ42 (PCN= 0.001; PMCI= 0.007), T-tau (PCN<0.001; PMCI<0.001), and Mid temporal (PCN= 0.033; PMCI= 0.005). Baseline CSF clusterin predicted measurable cognitive changes in the MCI population (MMSE, P = 0.029; MEM, P = 0.036; RAVLT immediate, P = 0.038; EF, P = 0.013; In MCI population, the alterations in brain regions (17.87% of the total effect) mediated the effect of clusterin on cognition. It was found that variables such as age, gender, and presence of APOE ε4 carrier status, influenced some of these connections.Conclusion: Our investigation underscored a correlation between CSF clusterin concentrations and pivotal AD indicators, while also highlighting clusterin's potential role as a protective factor for cognitive abilities in MCI patients.